Prevalence and changes in haemogram in sub-clinical ketosis in sheep reared under organized farming system - GUPTA, VINOD K; SHARMA, S D; VIHAN, V S; KUMAR, ASHOK (The Indian Journal of Animal Sciences, 2011)
Sheep (74) of Muzzafarnagri breed were screened in advance stage of pregnancy and early stage of lactation for prevalence of ketosis. The prevalence rate in relation to type of birth, kid's birth weight, dam's weight, age and breed, lactation number, feeding status, environmental stress, transportation and managemental variations was studied in organized farming system. The prevalence rate of sub-clinical ketosis was 14.86% in pregnancy, and 13.51%in lactation stage. The prevalence rate of sub-clinical ketosis was 13.89% in sheep giving birth to single lamb and it increased with increasing lamb's birth weight. The prevalence rate was positively correlated with dam's weight in both pregnancy and lactation. Similarly, age-wise distribution of data revealed that 3-4 years age group was the most susceptible for subclinical ketosis in pregnancy as well as during lactation periods. The prevalence rate in pregnant ewes was 50.00% and it increased with the increase i.n parity numbers in sheep. No clinical case was found in either goats or sheep based on overt signs of ketosis, but sub-clinical ketotic cases were identified on the basis of hypoglycemia «30 mg%) and ketonenlia. In normal physiological states (dry, pregnancy and lactation), erythrocytic indices (TEC, Hb and PCV) showed a declining trend on the values of these parameters during pregnancy and lactation states, which showed the state of anemia particularly in the last month of pregnancy. TLC levels increased in both pregnancy and lactation as compared to dry period. TEC, Hb, pev and Mev did not show any significant changes in sub-clinical ketotic cases in either species of animals under study compared to healthy group animals. The value of TEe, Hb and PCV were 8.26±O.61 and 6.81±O.341 xl06/J.lI, 6.70±O.20 and 6.28±0.33 g% and 25.20±O.70 and 25.38±0.38% in pregnancy and lactation in ketotic sheep respectively